AN ANALYSIS OF JUDICIAL DETERMINATIONS IN MARRIAGE DISPENSATION CASES FROM THE PERSPECTIVE OF MAQĀṢID AL-SHARĪ‘AH AND THE CHILD PROTECTION LAW - Muhammad Roy Purwanto; Nurul I’anatul Fajriyah (At-Thullab : Jurnal Mahasiswa Studi Islam, 2024)
This article aims to examine Judicial Determination Number 236/Pdt.P/2021/PA.Llk concerning a marriage dispensation issued by the Religious Court of Lolak, analyzed through the perspectives of Maqāṣid al-Sharī‘ah and the Child Protection Law. It explores how the judge resolved the petition for a marriage dispensation based on the conceptual considerations of Maqāṣid al-Sharī‘ah and Indonesia’s Child Protection Law. In cases related to marriage dispensations—particularly those involving underage marriages—judicial decisions are significantly influenced by the ethical framework of Maqāṣid al-Sharī‘ah. The overarching objectives of Islamic law, known as Maqāṣid al-Sharī‘ah, include the protection of wealth (māl), religion (dīn), life (nafs), intellect (‘aql), and lineage (nasl). These objectives guide judges in issuing rulings that uphold Islamic legal principles and promote the public interest. In this case, the Court received a petition from a father seeking a marriage dispensation for his 17-year-old pregnant daughter, registered under Case Number 236/Pdt.P/2021/PA.Llk. The Court assessed the couple’s eligibility to marry and the potential health risks concerning the girl, taking into account her survival, intellectual development, and lineage.